Using of economic profit parameters for construction of a regional rating of the Russian not public companies - СитникПетр Евгеньевич (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2010)
This clause examines the opportunity of calculation of a parameter of economic profit for the Russian companies which do not form their reporting under the international standards. The prologue of clause is devoted to an urgency of application of economic profit in domestic business. Today we can observe active inflow of the foreign capital in the Russian market; and as consequence value-based management (VBM) becomes more and more popular. Many large Russian firms have already declared process of transition in management to the value-based concept. Following course for not public and regional companies, which proprietors begin to understand opportunities of diversification with use of the financial market, and managing directors aspire to involve investment resources. Overall objective of the VBM assumes increase in well-being of owners of the company by means of maximization of value of the employed capital. Achievement of this purpose demands use of the new approach to management of firm and, hence, new parameters of productivity of its activity, capable to consider creation of additional cost. As a result of numerous researches it has been certain, that additional cost of the enclosed capital is created only when the profit earned by the company, exceeds alternative costs of use of the capital employed, later named by the cost of capital. Thus, for successful functioning the company should not become isolated on the analysis only the internal documentation and achieve excess of actual incomes over charges. On the contrary, it is necessary for it to consider market conditions which create the missed benefits in the form of alternative costs of using the invested capital in it. Modern approaches to VBM use parameter of economic profit. At calculation of a parameter of economic profit, the companies have faced a problem of incomparability of data. Cost of capital considers the profitableness received in the market on the basis of market value, and the net profit is an accounting parameter and pays off on the basis of balance value. As a result leading consulting agencies of the world had been created modern parameters of economic profit which in own way solve a problem incomparability data. Moreover, these companies have developed also concepts of management in cost on the basis of offered by each of them of a parameter of economic profit. The most known modern parameters of economic profit are: Economic Value Added, digging Stern Stuart, and Cash Value Added, offered Boston Consulting Group. But these parameters are based on International account standards of the reporting, that is why it complicates use of their techniques by the Russian not public companies. The main purpose of the article is calculation of economic profit for not public companies on the basis of data of the Russian financial reporting. The basic part of clause describes comparative analysis of the basic parameters of economic profit - residual income, economic value added and cash value added - from the point of view of their practical use for the not public companies. In the final part of this article the author offer the design procedure of parameters of economic profit according to the Russian reporting with use of the information of the share market. Ключевые слова: economic profit, financing policy, financial risk and risk management, capital and ownership structure.